Survival of Acacia leucophloea and Pterocarpus indicus Under Canopy of Acacia nilotica as Nurse Plants - Arnold C Hendrik; Yanti Daud (Foresty Faculty of Hasanuddin University, 2020)
Acacia nilotica which is a plants of the genus Acacia which is known as one of the invasive genera. A.niloticais very invasive due to several advantages it has such as very large seed production, seed dispersal far enough by wildlife, young plants to grow very fast and are resistant to drought and fire. Some invasive acacia species can act as nurse plants for native plants, which increases the photosynthetic efficiency of native plants, and protects native species from extreme temperatures. Therefore, it is important to know the chance of recolonizing native plants in areas that are invaded by foreign species, by looking at the performance of plants seedlings under A.niloticastands. This study aims to determine the potential of A.niloticainvasive plants as nurse plants for local plants in East Timor. The stages in this research are the preparation of tools and materials, seeding of target species, selection of A.niloticastands as a nurse plants, selection of healthy target species seedlings to be planted, planting of target species seedlings under A.niloticastands, observing survival ability and species growth target. An analysis of the survival ability of the seedlings was carried out using the Kaplan-Meier survival curve. The results of this study are the angsana seedlings and kabesak in this study experienced many deaths, external factors such as high-temperature factors due to the long dry season suspected to be the cause. A.niloticashade does not affect the survival of the angsana and kabesak seedlings, allelopathy produced byA.niloticaplants accompanied by a drought in a long period of time causes the plantsis unable to act as nurse plants for kabesak and angsana plants.